Inside out: the interrelationships of sustainable performance metrics and its effect on business decision making: theory and practice - Gong, Mengfeng; Simpson, Andrew; Koh, Lenny; Tan, Kim Hua (Elsevier, 2018)
There has been an increasing interest in the use of decision-making models to achieve sustainability goal in recent decades. However, a systematic review of performance metrics, which are an important element of decision-making models to evaluate the outcomes regarding firm’s economic, environmental and social performance, is lacking. This study provides critical reflections on the current state of literature and industry development regarding sustainable performance metrics and offers concrete suggestions to guide future research. This study contributes to existing studies by (1) exploring the interrelationship between sustainable triple-bottom performance in the decision making process; (2) integrating corporate governance mechanism into decision making process for sustainable consideration; and (3) conducting a comparison between academic theory and industry practice regarding the performance metrics proposed and employed